Makna Keterlibatan Orang Tua dalam Keberhasilan Intervensi Dini pada Anak Berkebutuhan Khusus: Studi Fenomenologi - Febrina Della; Sri Nurhayati Selian (Jurnal Pendidikan Kebutuhan Khusus, 2026)
This study aimed to explore the meaning of parental involvement in the success of early intervention for children with special needs. A qualitative research design with a phenomenological approach was employed. The study was conducted at an early intervention service institution in Banda Aceh City. The participants consisted of three parents of children with diverse special needs who were actively involved in early intervention programs. Participants were selected using purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings revealed four major themes: (1) parental involvement as a form of responsibility and affection; (2) collaboration with professionals as a supporting factor for successful intervention; (3) challenges experienced by parents during the intervention process; and (4) children's developmental progress as the meaning of successful early intervention. The study concludes that parental involvement is a continuous process and plays a crucial role in supporting children's development. Practically, these findings can guide early intervention institutions in developing family support programs (e.g., parent training and routine consultation) and encourage professionals to build more open, collaborative communication with parents as key partners in the intervention process.